2020
DOI: 10.1186/s12889-020-09501-y
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-randomised trial to test the effect of a behaviour change intervention on toilet use in rural India: results and methodological considerations

Abstract: Background Effective and scalable behaviour change interventions to increase use of existing toilets in low income settings are under debate. We tested the effect of a novel intervention, the ‘5 Star Toilet’ campaign, on toilet use among households owning a toilet in a rural setting in the Indian state of Gujarat. Methods The intervention included innovative and digitally enabled campaign components delivered over 2 days, promoting the upgrading of existing toilets to achieve use by all household members. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…The Swachh Bharat Mission is likely responsible for the increase in self-reported latrine use in control areas, but the increase in the intervention arms that was beyond that observed in the control arms can be attributed to the evaluated interventions. This finding is consistent with the results the individual studies reported in their independent analyses, which indicated positive effects on latrine use in Karnataka, Odisha, and Gujarat, with null effects in Bihar (Caruso et al, 2019b;Chuahan et al, 2019;Friedrich et al, 2019;International Initiative for Impact Evaluation, 2020;Schmidt, Wolf-peter, Chauhan et al, 2020;Viswanathan et al, 2019). However, the calculation of the average effect across all four studies has the added benefit of being both statistically more powerful and applicable to a broader set of contexts.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The Swachh Bharat Mission is likely responsible for the increase in self-reported latrine use in control areas, but the increase in the intervention arms that was beyond that observed in the control arms can be attributed to the evaluated interventions. This finding is consistent with the results the individual studies reported in their independent analyses, which indicated positive effects on latrine use in Karnataka, Odisha, and Gujarat, with null effects in Bihar (Caruso et al, 2019b;Chuahan et al, 2019;Friedrich et al, 2019;International Initiative for Impact Evaluation, 2020;Schmidt, Wolf-peter, Chauhan et al, 2020;Viswanathan et al, 2019). However, the calculation of the average effect across all four studies has the added benefit of being both statistically more powerful and applicable to a broader set of contexts.…”
Section: Discussionsupporting
confidence: 86%
“…This study builds on the work of the four independent impact (Caruso et al, 2019b;Chuahan et al, 2019;Friedrich et al, 2019;International Initiative for Impact Evaluation, 2020;Schmidt, Wolf-peter, Chauhan et al, 2020;Viswanathan et al, 2019). By using a common analytical approach to synthesize findings across studies, we are able to identify similarities in predictors of latrine use, such as sex and caste, and differences in predictors of latrine use, such as age, across these four states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the trial, no adverse events were reported. 31 and Gujarat (4•6%), 29 while the study in Bihar 32 reported null effects. Only the intervention in Karnataka aimed to increase safe disposal of child faeces, and found no effect.…”
Section: Resultsmentioning
confidence: 90%
“…Despite increased access to toilets, in many communities, complex sociocultural norms, along with technological and financial barriers, prevent individuals from using a toilet every time or exclusively using a toilet for defecation purposes [6][7][8]. Recent behavior change interventions designed to promote toilet use in rural India yielded, on average, a 5% increase in reported use amongst toilet owners, which is comparable to results generated by SBM [9][10][11]. Sustaining exclusive toilet use among all household members is a national priority for the current SBM 2.0, also known as the Open Defecation-Free plus scheme [12].…”
Section: Study Rationalementioning
confidence: 75%